DIGITALISASI BAGI PUSTAKAWAN GUNA PENYELAMATAN NASKAH KUNO DI PERPUSTAKAAN WILAYAH SURAKARTA - Andry Prasetyo (Abdi Seni, 2019)
AbstractThis paper describes the process of digitizing training for librarians to save and provide easy access for visitors, as well as a base for library digital libraries in the Surakarta Region. The training on media transfer and preparation of the E-Book uses participatory methods, namely librarians will be directly involved in the training process. The lack of knowledge of librarians in photographic technology as the basis of the digitization process (conversion of hard files into soft files), and the lack of budget allocations for digitalization are obstacles in saving ancient manuscripts. Therefore, it is necessary to make the right media transfer tool (reprograph). Librarians were finally able to understand the basic photography techniques and compilation of e-books with the PageFlip Book 3D application, so that a collection of manuscripts could be saved from extinction. Librarians get easy access to ancient manuscripts without having to touch physically with the original manuscript.Keywords: Digitalization, Ancient Manuscripts, Libraries, Surakarta.